Comparison of subjective and objective speaker recognition under voice disguise conditions - Majewski, Wojciech (Archives of Acoustics, 2007)
An experiment was performed in order to compare the results of subjective and objectivespeaker recognition under voice disguise conditions. The experimental material consisted ofthe key sentence “To jest akustyka” (Eng. “This is acoustics”) spoken several times by Polishmale speakers in a natural mode and under voice disguise conditions. In the subjective methodthe utterances were grouped in pairs and presented to the listeners whose task was to makea decision whether a given pair of speech samples was produced by one speaker or by twodifferent speakers. In the objective method two parametrical representations of speech (LPCcoefficients and Km reflection coefficients) were utilized and a computer program for automaticspeaker verification was applied. For normal speech both methods exhibited a very goodeffectiveness of speaker recognition and the results for the subjective method were a bit lower(98.9% in comparison to 99.4% for the objective method). Under voice disguise conditions,however, the mean results for the subjective method (92.3%) were substantially better than forthe objective one (77.2%).